(untitled) (Research, Society and Development, 2022)
Introduction: Physical Education is an important field of teaching and learning, it uses content that contributes to the development and social formation of the student, providing opportunities for experiences that help in the formation of reflective critical thinking, respect and cooperation. Objective: Show the contribution of Physical Education in the individual’s social formation. Methods: The study is characterized as a systematic review. To prepare the systematic review, a search was performed in the Scielo and Lilacs databases, including articles based on the inclusion criteria. Results: 56 articles were found in the first search phase. In the follow-up, a previous analysis of the articles found was carried out using the inclusion and exclusion criteria, resulting in only 3 articles included in the study. Conclusion: Physical Education has a relationship between the knowledge dealt with in class and understanding in multiple social dimensions. However, for the full development of the student, the Physical Education teacher must be committed to the real role of the educational process in the school environment.